Membrane fouling behavior and control strategies during ultrafiltration of polymer-flooding produced water - Mengyang He; Jun Xu; Jiahou Hao; Lai Lyu; Hongyuan Fang; Jing Lu; Dongsheng Zhao; Wenyu Zheng; Gengmin Jiang; Shuili Yu; Linna Wang (Journal of Environmental Chemical Engineering, 2026)

Synergistic application of biochar and compound microbial inoculant improves the performance of green waste composting - Cong Luo; Lu Zhang; Linna Suo; Lina Liang (Journal of Environmental Management, 2026)

Hydrogen peroxide–sodium carbonate pretreatment improves lignocellulose deconstruction and enzymatic saccharification of corn stover - Zejin Li; Zuhua Zhao; Lu Zhang; Linna Suo (Biomass and Bioenergy, 2026)

Accelerating green waste composting via in-situ photo-Fenton process: Enhanced lignocellulose degradation and microbial community dynamics - Kaiyi Zhang; Lu Zhang; Linna Suo; Lina Liang (Journal of Environmental Chemical Engineering, 2025)

Synergistic effects of malonic acid and biochar on carbon emission reduction, humification, and microbial regulation during green waste composting - Wenping Zhang; Lu Zhang; Linna Suo (Bioresource Technology, 2025)

Structural and functional alterations of human serum albumin (HSA) induced by TBBPS-BME: A spectroscopic, computational, and molecular dynamics study - Wei Zhang; Linna Gao; Shuyuan Zhang; Jiaqing Luo; Ruoxuan Yu; Xiting Li; Zhili Lu; Baozhu Chi; Ying Guo; Xun Tuo (Chemico-Biological Interactions, 2025)

Exploring efficient reductive dechlorination in nitrate-containing groundwater: Does sulfidated microscale zero-valent iron coupled with anaerobic bacteria increase sustainability? - Litao Wang; Linna Jia; Jia Xin; Lijun Chen; Weiran Meng; Jiahui Lu (Chemical Engineering Journal, 2024)

Performance comparison of anthocyanin-based smart indicator films - Zhigang Xiao; Linna Han; Mengqing Gu; Yiqun Zhu; Yifan Zhang; Zhe Li; Tiemin Xie; Fei Lu (Food Packaging and Shelf Life, 2023)

Assessing nickel sector index volatility based on quantile regression for Garch and Egarch models: Evidence from the Chinese stock market 2018–2022 - Linna Lu; Yalin Lei; Yang Yang; Haoqi Zheng; Wen Wang; Yan Meng; Chunhong Meng; Liqiang Zha (Resources Policy, 2023)

Stem Cell-derived Extracellular Vesicles: A Promising Nano Delivery Platform to the Brain? - Yuying Guo; Dongsheng Hu; Lu Lian; Linna Zhao; Mingli Li; Huijing Bao; Shixin Xu (Stem Cell Reviews and Reports, 2023)

Effects of water–nitrogen coupling on soil water and nitrogen, photosynthesis, yield and water use of lettuce under different application rates of poly‐γ‐glutamic acid - Lu Liu; Wenjuan Shi; Linna Pang (Irrigation and Drainage, 2023)
As an environmentally friendly, super water‐absorbable agent and fertilizer synergist, the influences of poly‐γ‐glutamic acid (γ‐PGA) on soil N and crop photosynthesis are still not well understood. A pot experiment was conducted to evaluate the effects of water–nitrogen coupling on soil water and nitrogen content, photosynthesis, yield and irrigation water use efficiency (IWUE) of lettuce under different γ‐PGA application rates. In this study, there were three factors and four levels: γ‐PGA with four application levels of 0, 1, 2 and 4 g kg −1 ; the rates of urea were 0, 0.2, 0.4 and 0.6 g kg −1 ; and the irrigation amounts were 40%, 60%, 80% and 100% of the lettuce water requirement (ET c ). The results showed that within 8 days after sowing, the soil water and nitrogen (NO 3 − ‐N and NH 4 + ‐N) content increased with increasing γ‐PGA application rates. The amount of irrigation water and nitrogen application had an effect on IWUE, net photosynthetic rate ( P n ) and stomatal conductance ( G s ). Lettuce yield was significantly correlated with P n , G s and intercellular CO 2 concentration ( C i ) by path analysis. Moreover, the P2N2W3 treatment (γ‐PGA 2 g kg −1 , nitrogen 0.2 g kg −1 and 80% ET c ) was the most suitable treatment to obtain the highest lettuce yield and IWUE.

Remote Estimation of the Chlorophyll-a Concentration in Lake Dianshan, China Using High-Spatial-Resolution Satellite Imagery - Xiaoman Lu; Chunyan Situ; Jiajia Wang; Liguo Zhou; Weichun Ma; Linna Li (Journal of the Indian Society of Remote Sensing, 2022)

Comparative analysis of four semi-analytical models for estimating chlorophyll- a concentration in case-2 waters using field hyperspectral reflectance - Xiaoman Lu; Chunyan Situ; Weichun Ma; Xiaoyan Dai; Cheng He; Linna Li; Liguo Zhou (International Journal of Remote Sensing, 2020)

Using magnetic susceptibility to evaluate pollution status of the sediment for a typical reservoir in northwestern China - Huiyun Pan; Xinwei Lu; Kai Lei; Dongqi Shi; Chunhui Ren; Linna Yang; Lijun Wang (Environmental Science and Pollution Research, 2019)

Accumulation and source of heavy metals in sediment of a reservoir near an industrial park of northwest China - Yuanjie Zhu; Xinwei Lu; Linna Yang; Lijun Wang (Frontiers of Earth Science, 2016)

De novo transcriptome sequencing in Ficus hirta Vahl. (Moraceae) to investigate gene regulation involved in the biosynthesis of pollinator attracting volatiles - Hui Yu; John D. Nason; Lu Zhang; Linna Zheng; Wei Wu; Xuejun Ge (Tree Genetics & Genomes, 2015)